Terminal differentiation and anti-tumorigenic effects of prolactin in breast cancer - Ali, Suhad; Hamam, Dana; Liu, Xueqing; Lebrun, Jean-Jacques (Frontiers in Endocrinology, 2022)
Breast cancer is a major disease affecting women worldwide. A woman has 1 in 8 lifetime risk of developing breast cancer, and morbidity and mortality due to this disease are expected to continue to rise globally. Breast cancer remains a challenging disease due to its heterogeneity, propensity for recurrence and metastasis to distant vital organs including bones, lungs, liver and brain ultimately leading to patient death. Despite the development of various therapeutic strategies to treat breast cancer, still there are no effective treatments once metastasis has occurred. Loss of differentiation and increased cellular plasticity and stemness are being recognized molecularly and clinically as major derivers of heterogeneity, tumor evolution, relapse, metastasis, and therapeutic failure. In solid tumors, breast cancer is one of the leading cancer types in which tumor differentiation state has long been known to influence cancer behavior. Reprograming and/or restoring differentiation of cancer cells has been proposed to provide a viable approach to reverse the cancer through differentiation and terminal maturation. The hormone prolactin (PRL) is known to play a critical role in mammary gland lobuloalveolar development/remodeling and the terminal differentiation of the mammary epithelial cells promoting milk proteins gene expression and lactation. Here, we will highlight recent discoveries supporting an anti-tumorigenic role for PRL in breast cancer as a “pro/forward-differentiation” pathway restricting plasticity, stemness and tumorigenesis.